Implementing Quality Service-Oriented Architecture Initiative in Organisations - Sulong, Muhammad Suhaizan; Koronios, Andy; Gao, Jing; Abdul-Aziz, Azlianor (2012)
Today, many organisations are facing business changes but their current systems are unable to adapt such changes. The reason is that the current architecture is monolithic in style which causes difficulties, costly and time consuming in response to changing business conditions. This is why organisations need to act on how to deal with this issue. A better way is to implement service-oriented architecture (SOA) initiative due to its benefits of achieving business agility. Although many organisations are succeeded in their SOA initiatives, many too are failed. One of the reasons to this failure is lack of information quality (IQ). Poor IQ includes inaccurate, incomplete and outdated information. The study aims to look at how can organisations manage and approach the quality of information to success in such initiatives. By reviewing literature, we have derived four key phases to implement SOA initiative and have discovered IQ management that can improve this implementation of SOA initiative. From the review, a research framework is constructed that seeks to identify IQ issues perceived to SOA initiative implementation with associated IQ requirements and appropriate IQ guidelines. It will then enable to design a model of SOA initiative with IQ management that can facilitate organisations in implementing SOA successfully. Further study would show if IQ can be extended to SOA initiative and thus may contributes in both IQ and SOA area of study.